2023
DOI: 10.3389/fpsyg.2023.1109149
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital empowerment on open innovation performance of enterprises from the perspective of SOR

Abstract: IntroductionAs China’s digital transformation index continues to climb and market openness increases, the active implementation of open innovation embedded in digital innovation eco-networks is key to implementing sustainable innovation-driven strategies. The widespread use of digital technologies has broken through the traditional closed boundaries of enterprises and enhanced technology exchange, information communication and R&D collaboration with other innovation agents.However, many enterprises’ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…Thus, these employee-centric initiatives significantly influence employees' empowerment and task accomplishment at the workplace. Furthermore, our findings are in line with existing research highlighting the relevance of digital skills training on employee empowerment and job performance (Lingling & Ye, 2023;Cirillo et al, 2023;Straub et al, 2023;Sam et al, 2022;Drydakis, 2022;Munawar et al, 2022;Monje Amor et al, 2021;Fawehinmi et al, 2020;Pham et al, 2020;Karacay, 2018). Also, the results of our study are in line with extant literature that highlights the importance of employees' access to digital platforms at the workplace on empowerment and job performance (Anderski et al, 2023;Jiang et al, 2023;Wang, Wan, Ma, Zhou & Chen, 2023;Bartczak, 2021;Sousa & Rocha, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, these employee-centric initiatives significantly influence employees' empowerment and task accomplishment at the workplace. Furthermore, our findings are in line with existing research highlighting the relevance of digital skills training on employee empowerment and job performance (Lingling & Ye, 2023;Cirillo et al, 2023;Straub et al, 2023;Sam et al, 2022;Drydakis, 2022;Munawar et al, 2022;Monje Amor et al, 2021;Fawehinmi et al, 2020;Pham et al, 2020;Karacay, 2018). Also, the results of our study are in line with extant literature that highlights the importance of employees' access to digital platforms at the workplace on empowerment and job performance (Anderski et al, 2023;Jiang et al, 2023;Wang, Wan, Ma, Zhou & Chen, 2023;Bartczak, 2021;Sousa & Rocha, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…It is essential in achieving efficiency, motivation and overall productivity of grassroots employees in this digital age (Peng & Tao, 2022). Employee digital empowerment requires providing and enabling workers with the digital resources, skills, and tools they need in order to use digital platforms and technology in their job efficiently so as to ensure tasks accomplishment at the workplace (Lingling & Ye, 2023). Based on several studies that have found significant mediating role of employee empowerment between structural empowerment and employees work effectiveness and productivity outcomes (Monje Amor et al, 2021;Hagerman et al, 2017;Hagerman, Skytt, Wadensten, Högberg & Engström, 2016;Meng, Jin & Guo, J.…”
Section: Mediating Role Of Employee Digital Empowermentmentioning
confidence: 99%
“…Second, Chaxu climate tends to engender disruptive social categorizations with status differences, attenuating the positive effects of cognitive diversity. Considering its widespread in Chinese organizations and easily recognized by employees [ 25 , 88 ], managers should pay close attention to initiatives that can decrease members’ shared perceptions of differential treatment. It is paramount to be transparent, objective, and fair when making human resource management (HRM) decisions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key problems is the contradiction between digital technologies and traditional management models. Expanding digital technologies, while offering numerous benefits, can also exacerbate existing challenges in organisational management (Lingling & Li, 2023). This highlights the need for organisations to adapt their management models to make effective use of digital technologies.…”
Section: Financial and Organisational Constraints In The Implementati...mentioning
confidence: 99%